2014
DOI: 10.1124/dmd.113.056663
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the HC-04 Cell Line as an In Vitro Model for Mechanistic Assessment of Changes in Hepatic Cytochrome P450 3A during Adenovirus Infection

Abstract: HC-04 cells were evaluated as an in vitro model for mechanistic study of changes in the function of hepatic CYP3A during virus infection. Similar to in vivo observations, infection with a first generation recombinant adenovirus significantly inhibited CYP3A4 catalytic activity in an isoform-specific manner. Virus (MOI 100) significantly reduced expression of the retinoid X receptor (RXR) by 30% 96 hours after infection. Cytoplasmic concentrations of the pregnane X receptor (PXR) were reduced by 50%, whereas th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 57 publications
0
5
0
Order By: Relevance
“…CYP3A11 mRNA levels were unaffected by AdDRGD throughout the study period. The observation that CYP3A activity was suppressed to a greater extent than protein and gene expression after infection with AdlacZ is not unique to these studies because it has previously been seen in vitro and could be attributable to post-translational modifications of the CYP3A enzyme (Wonganan et al, 2014).…”
Section: Integrins and Drug Metabolismmentioning
confidence: 80%
See 2 more Smart Citations
“…CYP3A11 mRNA levels were unaffected by AdDRGD throughout the study period. The observation that CYP3A activity was suppressed to a greater extent than protein and gene expression after infection with AdlacZ is not unique to these studies because it has previously been seen in vitro and could be attributable to post-translational modifications of the CYP3A enzyme (Wonganan et al, 2014).…”
Section: Integrins and Drug Metabolismmentioning
confidence: 80%
“…On a transcriptional level, hepatic CYP3A is constitutively expressed in the liver, but several nuclear receptors, including PXR, CAR, and RXR, are primarily responsible for regulating CYP3A gene expression (Croyle, 2009). However, it remains to be known which is predominantly influenced by virus infection and is ultimately responsible for our observed changes in CYP3A (Callahan et al, 2008a;Wonganan et al, 2014). In an effort to determine how integrin engagement changes each of these key regulators of CYP3A in vivo, gene and protein expression was determined 24 and 48 hours after infection with each virus (Fig.…”
Section: Integrins and Drug Metabolismmentioning
confidence: 99%
See 1 more Smart Citation
“…Some clinical research indicates that inhibitors of IL-6 enhance drug metabolism via CYP3A4, implying that IL-6 is an important regulator of this enzyme [ 396 ]. It has been demonstrated that CYP3A4 activity is suppressed in adenovirus-infected primary hepatocytes and that adenovirus-induced modification of PXR expression may be responsible for the alterations of CYP3A4 activity in the liver [ 397 ].…”
Section: Cyp3a Involvement In Pathological Processesmentioning
confidence: 99%
“…CYP1A1 activity was suppressed by 75% in coxsackievirus B3 infected mice (Funseth et al, 2002). CYP3A4 activity was suppressed in primary hepatocytes infected with adenovirus, and adenovirus-induced modification of PXR may be responsible for changes in hepatic CYP3A4 activity (Wonganan et al, 2014). CYP2A5 and CYP3A expression increased in hepatitis B virus (HBV)transgenic mice (Kirby et al, 1994), whilst CYP2D6 expression decreased in hepatitis C virus (HCV) infected mice (Kikuchi et al, 2010).…”
Section: Virus Infectionmentioning
confidence: 99%